LONG-TERM EFFECTS OF PYELOPLASTY IN CHILDREN WITH POORLY FUNCTIONING KIDNEYS: A RETROSPECTIVE STUDY. - Arshad , Jamal; Singh, Rana Pratap (Student's Journal of Health Research Africa, 2023)
Background: Pediatric pyeloplasty in ureteropelvic junction obstruction (UPJO) is indicated in renal impaired drainage or renal function deterioration. The improvement of renal function after pediatric pyeloplasty is still controversial in poorly functioning kidneys. Past studies on poorly functioning kidneys had a variable SRF specification, and these studies often had a limited number of patients so that they did not achieve statistical significance. Objective: The objective of this study was to assess the effectiveness and long-term results of pyeloplasty in children with poorly functioning kidneys. Method: Patients who underwent pyeloplasty at Department of Urology, Rajendra Institute of Medical Science, Ranchi for last twelve years were the subject of a retrospective data study. Postoperative outcome was the parameter under study. Success was measured by either symptom improvement or better drainage on postoperative Tc-99m DTPA renography, which was performed after two months and then yearly after that. Results: 60 individuals were enrolled in the study, with a mean age of 8.5 years (3 months to 12 years), a male-to-female ratio of 2:1, and poor function on the isotope renogram (31%). The ratio of left to right sides was 1.2:1. All patients had dismembered pyeloplasty procedures. 37 patients (66.8%) underwent laparoscopic pyeloplasty, whereas 23 (33.2%) underwent open surgery. 35 patients had follow-up renograms available; of these, 30 showed improved drainage and no further decline in renal function, while 5 displayed an obstructed pattern; of these, 3 patients had noticeably worsened split function, and the other two underwent a second open pyeloplasty. A mean follow-up of 21.5 months revealed a 91% overall success rate. Conclusion: In the pediatric age group, pyeloplasty provides satisfactory intermediate results in kidneys with inadequate function.